PKM (COMMUNITY PARTNERSHIP PROGRAM) CHILDRENS DEVELOPMENT IN PONGKOWULU VILLAGE NORTH BUTON REGENCY - La Jeti; Manan Manan; Sartina Sartina; Wa Ode Sartika (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Education for early childhood plays a very important role in the formation of the next generation successor of the Indonesian nation in the future. Early childhood is part of the resource human beings that require serious and sustainable handling by all parties who have shared responsibility for the formation of a quality next generation. To ensure To succeed in getting this quality next generation, actions are needed by those who are actively engaged in the world of education. The objectives of this service was Understanding in development of children and parenting models in developing children's character, using methods, socialization guidance and resulted that the implementation of Organizing program socialization with related parties and creating development methods learning for children through parents engagement, School Engagement, and School Engagement with Community. Participants in the training are very enthusiastic about participating in socializing character development children as well as assisting ECE institutions as participants in the character development training for ECE.